2014
DOI: 10.1016/j.numecd.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of waist-to-height ratio to predict 5 year cardiometabolic risk in sub-Saharan African adults

Abstract: The WHtR threshold of >0.5 appears to be more consistently supported and may provide a better predictor of future cardiometabolic risk in sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 26 publications
7
33
1
2
Order By: Relevance
“…WHtR has been found previously to align well across different age groups, genders and ethnicities, which is in agreement with our findings. A meta‐analysis of elderly individuals showed that WHtR was a better predictor of cardiovascular risk in younger elderly individuals compared to older elderly individuals .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…WHtR has been found previously to align well across different age groups, genders and ethnicities, which is in agreement with our findings. A meta‐analysis of elderly individuals showed that WHtR was a better predictor of cardiovascular risk in younger elderly individuals compared to older elderly individuals .…”
Section: Discussionsupporting
confidence: 94%
“…Models were adjusted for age, sex, current smoking status, Asian region, randomized blood pressure-lowering intervention and randomized glucose control intervention. Values were trimmed at less than 1st percentile and greater than 99th percentile of each obesity index WHtR has been found previously to align well across different age groups, genders and ethnicities, 12,27,28 which is in agreement with our findings. A meta-analysis of elderly individuals showed that WHtR was a better predictor of cardiovascular risk in younger elderly individuals compared to older elderly individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…b African specific WC cut-off point for central obesity [25]. c African specific [27] cut-off point for central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…African specific cut-offs were used to indicate abdominal obesity [26]. An additional relatively new indicator of central obesity; waist: height ratio (WHtR) was calculated with the formula WHtR = WC (cm)/height (cm) and used in conjunction with WC to indicate central obesity also using African specific cut-offs [27]. A Harpenden caliper (Baty International West Sussex, UK) was used to measure skinfolds (triceps, chest, abdominal, thigh and supra iliac).…”
Section: Anthropometric Measurementsmentioning
confidence: 99%